2018
DOI: 10.1016/j.clim.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high glucose on cytokine production by human peripheral blood immune cells and type I interferon signaling in monocytes: Implications for the role of hyperglycemia in the diabetes inflammatory process and host defense against infection

Abstract: The major metabolic feature of diabetes is hyperglycemia which has been linked to the diabetes inflammatory processes, and diabetes-related vulnerability to infection. In the present study, we assessed how glucose affected PBMCs in type I interferon (IFN) production and subsequent signaling. We found that the moderately elevated glucose promoted, and high glucose suppressed type I IFN production, respectively. Pre-exposure to high glucose rendered monocytes more sensitive to IFN-α stimulation with heightened s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 54 publications
1
62
0
1
Order By: Relevance
“…Hu et al have shown that polyinosinic:polycytidylic acid (polyI:C), a Toll-like receptor 3 (TLR3) agonist, stimulated PBMCs in HG medium (24 mM glucose), while cells cultured in LG produced significantly lower levels of type I IFNs ( 125 ). Additionally, they indicated that under these conditions PBMCs express elevated levels of IFN-γ, IL-1β, IL-6, IL-10, granulocyte-macrophage colony-stimulating factor (GM-CSF), TNF-α, RANTES/CCL5 (Regulated on Activation, Normal T cell Expressed and Secreted), and macrophage inflammatory protein (MIP)-1α ( 125 ). Hu et al have also shown that HG in T2DM patients decreases the formation, viability, differentiation and functions of osteoclasts, which are bone-resident innate immune cells ( 126 ).…”
Section: Effects Of T2dm On the Immune Systemmentioning
confidence: 99%
“…Hu et al have shown that polyinosinic:polycytidylic acid (polyI:C), a Toll-like receptor 3 (TLR3) agonist, stimulated PBMCs in HG medium (24 mM glucose), while cells cultured in LG produced significantly lower levels of type I IFNs ( 125 ). Additionally, they indicated that under these conditions PBMCs express elevated levels of IFN-γ, IL-1β, IL-6, IL-10, granulocyte-macrophage colony-stimulating factor (GM-CSF), TNF-α, RANTES/CCL5 (Regulated on Activation, Normal T cell Expressed and Secreted), and macrophage inflammatory protein (MIP)-1α ( 125 ). Hu et al have also shown that HG in T2DM patients decreases the formation, viability, differentiation and functions of osteoclasts, which are bone-resident innate immune cells ( 126 ).…”
Section: Effects Of T2dm On the Immune Systemmentioning
confidence: 99%
“…24 Another study performed on human peripheral blood mononuclear cells and human monocyte cell lines in vitro showed that hyperglycemia suppressed IFN-1 production and that pre-exposure to high glucose concentrations rendered monocytes more sensitive to IFN-α stimulation with heightened signaling. 25 Additionally, they found that high glucose levels promoted the production of other pro-inflammatory cytokines. 25 Therefore, it is probable that patients with T2DM may have alterations in their innate immune system that promotes proinflammatory cytokines as well as having a defective host defense system against viral infections by impeding IFN-1 production and signaling.…”
Section: Increased Susceptibility Of Patients With T2dm To Infectionsmentioning
confidence: 99%
“…25 Additionally, they found that high glucose levels promoted the production of other pro-inflammatory cytokines. 25 Therefore, it is probable that patients with T2DM may have alterations in their innate immune system that promotes proinflammatory cytokines as well as having a defective host defense system against viral infections by impeding IFN-1 production and signaling.…”
Section: Increased Susceptibility Of Patients With T2dm To Infectionsmentioning
confidence: 99%
“…Leptin affects fat and glucose metabolism and is linked to elevated free fatty acids and glucose levels in obesity and diabetes ( 38 ). Such high levels of glucose suppress the anti-viral type 1 IFN production in PBMCs ( 41 , 42 ) and increase the reactive oxygen species in T cells ( 43 ). Elevated free fatty acids activate TLRs, induce inflammatory cytokines in circulating monocytes and enhance inflammation in T cells ( 44 47 ).…”
Section: Obesity and Immune Systemmentioning
confidence: 99%